2020
DOI: 10.1055/s-0040-1705124
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Chiral Amplification in Luminescent Supramolecular Polymers Based on Trisbiphenylamine-tricarboxamides

Abstract: We describe the synthesis of two propeller-shaped, emissive trisbiphenylamines 1 and (S)-2. Whilst achiral 1 forms supramolecular polymers following a cooperative mechanism, the self-assembly of chiral (S)-2 can be described by an isodesmic mechanism. Despite the isodesmic character of the supramolecular polymerization of (S)-2, an efficient transfer of chirality from the embedded point chirality of the peripheral side chains to the aggregates is demonstrated. The co-assembly of 1 and (S)-2 in a sergeants-and-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…However, an analogous effect but of opposite sign is observed for the SaS experiments carried out by mixing 1 and ( S ) - 1 (Figure S18). We have previously described a similar effect for self-assembling units able to form intramolecular hydrogen-bonded metastable monomers that retard the corresponding supramolecular polymerization . However, this is not the case, since N-annulated PBIs 1 cannot form H-bonded metastable monomers and their supramolecular polymerization is under thermodynamic control.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, an analogous effect but of opposite sign is observed for the SaS experiments carried out by mixing 1 and ( S ) - 1 (Figure S18). We have previously described a similar effect for self-assembling units able to form intramolecular hydrogen-bonded metastable monomers that retard the corresponding supramolecular polymerization . However, this is not the case, since N-annulated PBIs 1 cannot form H-bonded metastable monomers and their supramolecular polymerization is under thermodynamic control.…”
Section: Resultsmentioning
confidence: 98%
“…We have previously described a similar effect for self-assembling units able to form intramolecular hydrogen-bonded metastable monomers that retard the corresponding supramolecular polymerization. 25 However, this is not the case, since N-annulated PBIs 1 cannot form H-bonded metastable monomers and their supramolecular polymerization is under thermodynamic control. A similar abnormal SaS effect has been described for covalent polymers and justified by considering the different energy preferences exhibited by the situation in which a chiral sergeant is adjacent to another chiral sergeant or to an achiral soldier.…”
Section: Resultsmentioning
confidence: 99%
“…Such cores have already demonstrated their potential as optoelectronic 31 and supramolecular materials. 32 34 …”
Section: Resultsmentioning
confidence: 99%
“…Thus, we opted for a partially O -bridged triphenylborane ( S -B1 ) whose electron-rich environment and structural rigidity impart higher stability to the boron center when compared to those of nonbridged analogues. ,, Bridged triarylboranes have been recently introduced as a new class of stable, organic electronic materials by one of us. , On the basis of the design of S -B1 , two N cores were synthesized: (i) an analogous partially O -bridged triphenylamine, S -N1 , and (ii) a triphenylamine core, S -N2 and a-N2 . Such cores have already demonstrated their potential as optoelectronic and supramolecular materials. …”
Section: Resultsmentioning
confidence: 99%
“…In 1989, Green and co-workers reported that copolymers of an achiral isocyanate with a small fraction of a chiral isocyanate exhibit a disproportionate helical bias. This phenomenon is called the sergeants-and-soldiers (S&S) effect, and numerous subsequent studies have shown that it is applicable to both covalent and supramolecular polymers.…”
Section: Introductionmentioning
confidence: 99%